(untitled) (Global Journal of Science Frontier Research, 2012)
Behavioral response, Acetylecholinesterase activity, total protein level and protein fractions of the Nile tilapia, Oreochromis niloticus were investigated after 37 days exposure period to different environmental colors (Yellow, blue, green, red and darkness). Groups of 10 individuals each with initial body weight of 10.01±0.15 g were reared in 60x30x50 cm) aquarium. Two replicate groups for each color were covered with blue, green, red or black cellophane (no cellophane was used for yellow light). Fish Behavior was observed daily in the containers. Enzyme activity, mortality, total protein, albumin/globulin ratio and protein fractions were measured in 7, 37 and 45 days (7 days recovery). Results showed different behavioraland biological changes in responce to the change of color in all tested parameters. Mortality ratios were also affected by changes in surrounding color. Fish showed preference for blue light followed by green light, while red light was the most unfavorable to fish. Therefore, authors recommend applying blue color lighting in aquaculture system in order to obtain the best conditions for fish production.